2012
DOI: 10.1111/j.1524-475x.2012.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Simple wound exudate collection method identifies bioactive cytokines and chemokines in (arterio) venous ulcers

Abstract: A major challenge for clinicians treating (arterio) venous leg ulcers is to decide between standard therapy and advanced interventions. Here, we developed a simple method to collect human material representative of the ulcer wound bed, which can be used to identify biomarkers for prognostic test development. Superficial surgical debridement was performed using a small vidal curette during the weekly visit to the outpatient clinic. Moist, easily removable debridement material essentially blood free (including n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 41 publications
1
22
0
4
Order By: Relevance
“…21 This receptor is expressed in many cells, including keratinocytes, dermal fibroblasts, and ASC. 3,24 Since we previously detected this chemokine also in chronic wound exudates, 10 it is most probable that it is related to skin trauma in general. However, the function of this skin-specific chemokine during wound healing is still unknown.…”
Section: Cd4mentioning
confidence: 91%
See 1 more Smart Citation
“…21 This receptor is expressed in many cells, including keratinocytes, dermal fibroblasts, and ASC. 3,24 Since we previously detected this chemokine also in chronic wound exudates, 10 it is most probable that it is related to skin trauma in general. However, the function of this skin-specific chemokine during wound healing is still unknown.…”
Section: Cd4mentioning
confidence: 91%
“…3 In addition, we have shown that both ASC and dermal fibroblasts migrate predominantly toward chemokine CCL5, 3 which is present in the wound fluid of chronic cutaneous wounds. 10 However, it is still unclear how the migrated ASC and dermal fibroblasts respond to wound-healing mediators that are present in the wound bed. Generally, skin substitutes (SS) contain dermal fibroblasts and keratinocytes.…”
mentioning
confidence: 99%
“…Furthermore, elevated levels of CXCL8 have been described to contribute to delayed wound healing, as CXCL8 was increased in non‐healing human thermal wounds compared with healing wounds. High amounts of CXCL8 and IL‐6 were detected in wound extracts of non‐healing ulcers (Kroeze et al, 2012b). However, it has also been described that tumour necrosis factor‐α stimulates oral keratinocytes to produce more CXCL8 and IL‐6 than skin keratinocytes (Li, Farthing, Ireland, & Thornhill, 1996a; Li, Ireland, Farthing, & Thornhill, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ulcers are difficult to heal spontaneously due to their characteristics of low cellular proliferation rates, 1-3 low cellular migration capacities, [3][4][5] followed by cellular senescence of fibroblasts on their wound bed and edges. 3,6 All of these may be caused by lack of growth factor supplies 7,8 as they are indicated by the decrease of GF-gene expressions among diabetic patients who tend to have chronic ulcers, 9 the entrapment of GFs by fibrin that spill out when capillaries leak due to high venous pressure in patients with venous leg ulcers, 7,10,11 and GFs degradation by protease contained in bio-film on the surface of chronic ulcer.…”
Section: Introductionmentioning
confidence: 99%